Lossless 4D Medical Images Compression Using Adaptive Inter Slices Filtering - Leila Belhadef; Zoulikha Mekkakia Maaza (International Journal of Advances in Applied Sciences, 2018)
Recent lossless 4D medical images compression works are based on the application of techniques originated from video compression to efficiently eliminate redundancies in different dimensions of image. In this context we present a new approach of lossless 4D medical images compression which consists to application of 2D wavelet transform in spatial directions followed or not by either lifting transform or motion compensation in inter slices direction, the obtained slices are coded by 3D SPIHT. Our approach was compared with 3D SPIHT with/without motion compensation. The results show our approach offers better performance in lossless compression rate.